<span>y=x+16
y=-x+4
All you have to do is substitute.
Put the second equation into the first equation.
-x + 4 = x + 16
4 = 2x + 16
-12 = 2x
-6 = x
Now substitute the x into one of the equations to get y.
y = (-6) + 16
y = 10
The solution to these equations is (-6, 10).</span>
Answer:
8cx + 12c
Step-by-step explanation:
Multiply the parentheses by 4 and then calculate the products
I need help to find the root?
Answer:
Yes it is biased
Step-by-step explanation:
It shows favoritism
Answer: the last option.
A binomial experiment is an experiment with only two possible outcomes.
In the first option, there is three possible outcomes (i.e. A, B, C)
In the second option, there is four poissible outcomes (i.e. ace, king, queen, jack)
The third option has six possible outcomes (i.e. six faces of a die)
In the last option, there are two possible outcomes (i.e. '2 number cubes')